Democracia; paridad de género y cambio. Un espacio institucional para las relaciones de género. (2013)
In this article; I examine how gender parity is a viable mechanism to protect the capacity of transformation that characterizes democracy. Fundamentally; I contend that a democratic system needs to provide arenas of deliberation in order to contest gender relations and eradicate practices of domination. Moreover; I argue that the exclusion and censorship of groups that question the predominant gender practices contradicts the spirit of democracy. Therefore; if women do not find institutional paths to express their ideas and to materialize their desires and beliefs; democratic institutions must be designed so as to enable these processes of inclusion.